The Effect of Work Life Balance and Self-Efficacy on Employee Performance Through Organizational Commitment - Asti, Viona Dara; Nasution, Nasution (Universitas Negeri Semarang, 2025)
The purpose of this study is determine how work life balance and self efficacy impact employee performance, either directly or through organizational Commitment. In facing fiercer industrial competition, employee performance plays a vital role in boosting the banking sector's competitiveness. This research uses quantitative approach and applies the simple random sampling method in sampling. The subjects of this study were 128 respondents selected as a sample from the population of Bank Bengkulu employees in the Bengkulu City area, totaling 423 people. Data collection was conducted straightforwardly utilizing customary (paper) surveys. In differentiation, data examination conducted through the Structural Equation Modeling strategy based of Partial Least Squares utilizing SmartPLS version 3.0 software. Outcomes of analysis show that work-life balance and self efficacy significantly and favorably affect employee performance, either directly or through organizational commitment. In addition, organizational commitment strengthens the impact of these two variables on improving performance. The implication of this research is that the management of Bank Bengkulu needs to improve work-life balance and employee self-efficacy to strengthen organizational commitment, so that employee performance can be optimal and company productivity increases.